Insights Into the Cultivable Microbial Ecology of “Manna” Ash Products Extracted From Fraxinus angustifolia (Oleaceae) Trees in Sicily, Italy - Guarcello, Rosa; Gaglio, Raimondo; Todaro, Aldo; Alfonzo, Antonio; Schicchi, Rosario; Cirlincione, Fortunato; Moschetti, Giancarlo; Francesca, Nicola (Frontiers in Microbiology, 2019)
Microbial communities characterizing a specific food matrix, generally, strongly contribute to both its composition and properties for food applications. To our knowledge, this is the first study to investigate the cultivable microbial ecology of Sicilian “Manna” ash products in order to acquire new information on the hygienic quality, shelf-life and potential application of this traditional food. To this purpose, several manna samples belonging to different commercial categories were collected and subjected to the analysis of bacteria, yeasts and filamentous fungi. Furthermore, an investigation of the sugar content and physicochemical parameters was performed. The results of our study followed the trend generally reported for other sugary foods. Conversely, as regards microbiological analyses, in the present study, the presence of microorganisms at high levels confirmed their survival in stressing conditions characterizing this food matrix in a viable and cultivable form. Most species were osmophilic, endophytic bacteria antagonistic of fungi pathogen of plants. Yeasts were the most abundant microbial populations and a total of six species were identified: Candida aaseri, Candida lactis-condensi, Citeromyces matritensis, Lachancea thermotolerans, Saccharomyces cerevisiae and Zygosaccharomyces bailii. Filamentous fungi included five genera, considered common contaminants of honey and of others foods due to their xerophilic characteristics. Interestingly, our results suggest that the strains of L. thermotolerans isolated in this study might be evaluated for their potential to act as starters either singly or in multi-combination for food applications.